Analysis of biophysical parameters (vegetation and land surface temperature) with satellite images using the Google Earth Engine platform - Rocha, Bruna (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
Urbanization exerts ecological and climatic impacts, and one of which is the increase in Land Surface Temperature (LST) in urban environments. Remote sensing enables the acquisition of satellite data capable of providing historical and current information from various regions worldwide. In addition to LST information, the identification of photosynthetically active vegetation is achievable through the application of the Normalized Difference Vegetation Index (NDVI). This study investigated the patterns of land surface temperature and their relationship with the vegetation index in areas influenced by urbanization in the city of Joinville - SC, using the Normalized Difference Vegetation Index (NDVI) as a biophysical parameter of surface emissivity. The Google Earth Engine (GEE) platform was used for the main processes and calculations, enabling access to cloud-based datasets from the Landsat 8 collection. The LST was obtained through surface emissivity, extracted via NDVI. The results indicate higher LST values in impermeable environments, with little or no vegetation. Thus, the research demonstrated that higher LST values result from the influence of lower NDVI values, highlighting the relevance of green areas in built environments.